Angiopoietin-1 Mimetic Peptide Promotes Neuroprotection after Stroke in Type 1 Diabetic Rats. Issue 12 (December 2018) - Venkat, Poornima; Yan, Tao; Chopp, Michael; Zacharek, Alex; Ning, Ruizhuo; Van Slyke, Paul; Dumont, Daniel; Landschoot-Ward, Julie; Liang, Linlin; Chen, Jieli
Angiopoietin-1 (Ang1) mediates vascular maturation and immune response. Diabetes decreases Ang1 expression and disrupts Ang1/Tie2 signaling activity. Vasculotide is an Ang1 mimetic peptide, and has anti-inflammatory effects. In this study, we test the hypothesis that vasculotide treatment induces neuroprotection and decreases inflammation after stroke in type 1 diabetic (T1DM) rats. T1DM rats were subjected to embolic middle cerebral artery occlusion (MCAo) and treated with: 1) phosphate buffered saline (PBS); 2) vasculotide (3µg/kg, i.p. injection) administered half an hour prior to MCAo and at 8 and 24 hours after MCAo. Rats were sacrificed at 48 h after MCAo. Neurological function, infarct volume, hemorrhage, blood brain barrier (BBB) permeability and neuroinflammation were measured. Vasculotide treatment of T1DM-MCAo rats significantly improves functional outcome, decreases infarct volume and BBB permeability, but does not decrease brain hemorrhagic transformation compared with PBS-treated T1DM-MCAo rats. In the ischemic brain, Vasculotide treatment significantly decreases apoptosis, number of cleaved-caspase-3 positive cells, the expression of monocyte chemotactic protein-1 (MCP-1) and tumor necrosis factor (TNF-α). Western blot analysis shows that vasculotide significantly decreases expression of receptor for advanced glycation end products (RAGE), MCP-1 and TNF-α in the ischemic brain compared with T1DM-MCAo rats. Vasculotide treatment in cultured primary cortical neurons (PCN) significantly decreases TLR4 expression compared with control. Decreased neuroinflammation and reduced BBB leakage may contribute, at least in part, to vasculotide-induced neuroprotective effects after stroke in T1DM rats.